Sex ratio and age in human populations - Promińska, Elżbieta (Anthropological Review, 1981)
The author has reviewed the literature dealing with sex ratios in human populations. She has concentrated on following problems: factors differentiating frequency of male and female conceptions, correlations between sex of offspring and physical characteristics of parents, demographical consequences of varying sex ratios.